Isolated central nervous system relapse of chronic myeloid leukemia after allogeneic hematopoietic stem cell transplantation - Fuchs, Mary (BioMed Central, 2012)
BACKGROUND: This case report highlights the relevance of quantifying the BCR-ABL gene in cerebrospinal fluid of patients with suspected relapse of chronic myeloid leukemia in the central nervous system. CASE PRESENTATION: We report on a female patient with isolated central nervous system relapse of chronic myeloid leukemia (CML) during peripheral remission after allogeneic hematopoietic stem cell transplantation. The patient showed a progressive cognitive decline as the main symptom. MRI revealed a hydrocephalus and an increase in cell count in the cerebrospinal fluid (CSF) with around 50% immature blasts in the differential count. A highly elevated BCR-ABL/ ABL ratio was detected in the CSF, whilst the ratio for peripheral blood and bone marrow was not altered. On treatment of the malresorptive hydrocephalus with shunt surgery, the patient showed an initial cognitive improvement, followed by a secondary deterioration. At this time, the cranial MRI showed leukemic infiltration of lateral ventricles walls. Hence, intrathecal administration of cytarabine, methotrexate, and dexamethasone was initiated, which caused a significant decrease of cells in the CSF. Soon after, the patient demonstrated significant cognitive improvement with a good participation in daily activities. At a later time point, after the patient had lost the major molecular response of CML, therapy with dasatinib was initiated. In a further follow-up, the patient was neurologically and hematologically stable. CONCLUSIONS: In patients with treated CML, the rare case of an isolated CNS blast crisis has to be taken into account if neurological symptoms evolve. The analysis of BCR-ABL in the CSF is a further option for the reliable detection of primary isolated relapse of CML in these patients.